Postmortem distribution of dihydrocodeine and metabolites in a fatal case of dihydrocodeine intoxication - Skopp, Gisela; Klinder, Klaus; Pötsch, Lucia; Zimmer, Gisela; Lutz, Rainer; Aderjan, Rolf; Mattern, Rainer (Forensic science international, 1998)
A report of a fatal dihydrocodeine ingestion under substitution therapy is given. Quantitation of dihydrocodeine, dihydromorphine, N-nordihydrocodeine, dihydrocodeine-6-, dihydromorphine-6- and dihydromorphine-3-glucuronide was performed simultaneously after solid-phase extraction prior to HPLC analysis, and the analytes were detected using their native fluorescence. Postmortem concentrations of blood samples from different sampling sites as well as from liver, kidney and cerebrum are reported. A hair sample was investigated to prove long-term use of the substitute drug. Site-to-site differences of the analytes from blood samples were very small. The partition behavior of the opioid glucuronides depended on the hematocrit value of the particular blood sample. Most important findings seemed that dihydromorphine and dihydromorphine-6-glucuronide concentrations decisively contributed to the toxicity of dihydrocodeine. This case report outlines that in dihydrocodeine related deaths the concentrations of the pharmacologically active metabolites should additionally be determined for reliable interpretation.